Flowering and fruiting phenology of Solanum mauritianum – a potential invasive alien species in the upcountry wet zone of Sri Lanka - L. Sarvananda; D.C.N.A. Wickramarathne; J.D. Kottawa-Arachchi; H.A.C.K. Ariyarathna (Silva Balcanica)
First comprehensive investigation of Solanum mauritianum in Sri Lanka, focusing on its invasive potential, ecological traits, and management challenges in the upcountry wet zone. Field surveys (2016–2018) along the A7 road from Peradeniya to Horton Plains National Park documented rapid colonization of roadsides, agricultural lands, and disturbed habitats, driven by prolific seed production (100,000–200,000 seeds annually per mature plant), vegetative propagation, and long-distance dispersal via frugivorous birds. Phenological analyses revealed seasonal fruiting peaks (April and August) linked to temperature and humidity fluctuations, with seed dormancy broken under 12 hr light/dark cycles and gibberellic acid treatment. Self-pollination, generalist pollinator interactions, and genetic diversity (assessed via RAPD markers) further facilitated invasiveness, showing genetic clustering in-dependent of geographic distance. Despite toxicity, farmers utilize the species for crop support, though its aggressive growth threatens native biodiversity by displacing flora. Conventional control methods, such as herbicides, proved ineffective due to rapid regrowth, while pre-fruiting uprooting and community-led management emerged as viable strategies. Community engagement enhanced data collection and invasive species awareness, underscoring participatory conservation’s value. As the first study of S. mauritianum in Sri Lanka, this work highlights its dual role as an ecological disruptor and a resource with localized agricultural utility, emphasizing the need for adaptive management. Future research should prioritize long-term ecological impacts, biological control agents, and climate adaptation studies to refine sustainable solutions. The findings provide foundational insights for invasive species management in Sri Lanka’s biodiverse ecosystems.